Умови формування межі колекторів газу в пісковиках локальних антиклінальних структур Донбасу - Лукінов, В.; Безручко, К. (Геологія і геохімія горючих копалин, 2010)
Розглянуто можливість існування газових скупчень у локальних антиклінальних
структурах вугленосної товщі Донбасу щодо наявності зони розущільнення та порід
з екранувальною здатністю, які можуть слугувати покришкою (екраном). Екранувальна здатність порід розглядається за їхньою абсолютною проникністю та тиском
прориву, потрібним для фільтрації флюїдів. Розраховано значення тисків прориву
відповідно до абсолютної проникності по газу. Згідно з розрахунками, породи з абсолютною проникністю 10⁻¹⁶ м²
здатні витримувати надлишковий тиск до 2,0 МПа, з
проникністю 10⁻¹⁷ м²
– до 4,4 МПа. Для порід з абсолютною проникністю 10⁻¹⁸ м²
тиск прориву має становити не менше ніж 9,8 МПа. Розглянуто механізм виникнення надлишкового тиску під час складкоутворення. Оцінено можливі пластові тиски
в локальних антиклінальних структурах. Значення пластових тисків розраховували
з допомогою коефіцієнта аномальності за емпіричною формулою, отриманою для
Дніпровсько-Донецької западини.
Коефіцієнт аномальності – це відношення початкового пластового тиску до гідростатичного для відповідної глибини. Його значення залежить від інтенсивності
складкоутворення, яку, у свою чергу, визначають за параметрами структури – висотою та площею. Аномально високі пластові тиски для структур Донбасу за розрахунками можуть характеризуватися максимальними значеннями коефіцієнта аномаль-
ності 1,31–1,40. Середнє значення – 1,17. Отримані аналітичні результати цілком
збігаються з фактичними замірами пластових тисків. На глибинах 500–2500 м перепад тиску може становити в середньому від 0,875 до 4,375, максимально – до
1,750–8,750 МПа. Середнім значенням надлишкових тисків відповідають породи з
проникністю 10⁻¹⁶–10⁻¹⁷ м²
, максимальним – 10⁻¹⁷–10⁻¹⁸ м²
. Зроблено висновок, що непорушені під час складкоутворення шари пісковику можуть слугувати екраном газового покладу за мінімальних значень тиску, потрібного для прориву флюїдів, тобто
за абсолютної проникності 10⁻¹⁶ м²
(десяті частки мілідарсі). The article is devoted to the ground of forming and conservation conditions of hydrocarbons accumulations in a Carboniferous massif, with the purpose of actual scientific
problem decision – prognosis estimation of low-porous terrigenous rocks perspective in
the local anticlinal structures of Carboniferous strata.
It has been proved that at a tension which has overrided overall significance for violation of wholeness and minimum fragile deformations of break, the filtration properties
which correspond to the industrial collectors of the IV class, favourable for the methane
accumulation, are formed in low-porous sandstones due to crevice deformation. It is
shown that formation of gas accumulations takes a place as a result of phases redistribution in consequence of system “water–gas” in the rock massif aspiring to the equilibrium.
The conditions of gas accumulations formation and conservation were grounded and
the parameters of screen properties were estimated, which characterize collector-screen
limit and screens in carboniferous deposit.
Possibility of gas accumulations existence in Donbas local anticlinal structures has
been considered from the view-point of the presence of volume expansion zone and rocks
with shielding ability, which can serve as cover and (or) screen. Shielding ability of rocks
is considered under their absolute permeability and inrush pressure, necessary for fluids
filtration. Inrush pressures values were rated in accordance with absolute gas permeability.
According to calculations, rocks with absolute permeability 10⁻¹⁶m²
are able to stand excess pressure to 2.0 MPa, with absolute permeability 10⁻¹⁷ m² to 4.4 MPa. For rocks with absolute permeability 10⁻¹⁸ m²
inrush pressure may be not less than 9.8 MPa. Mechanism
of excess pressure initiation in fold formation process was considered. Possible layer pressures were estimated in local anticlinal structures. Values of layer pressures were calculated with help of abnormality coefficient under empiric formula, obtained for DnieperDonets Depression. Abnormality coefficient is initial layer pressure ratio to hydrostatic for
the proper depth. Its value depends on fold formation intensity. Fold formation intensity,
in its turn, is determined under parameters of local structure – height and area. Abnormally high formation pressures for Donbas real structures according to calculations can be
characterized by maximal values of abnormality coefficient 1.31–1.40. Mean value for
Donbas is 1.17. Obtained analytical results completely coincide with actual metering of
layer pressures. At depths of 500–2500 m differential pressure can make up on average
from 0.875 to 4.375 MPa, maximum to 1.750–8.750 MPa. Rocks with 10⁻¹⁶
–10⁻¹⁷ m² permeability correspond to mean value of excess pressures, maximum – 10⁻¹⁷ – 10⁻¹⁸ m². The conclusion has been made that unmoved sandstones layers in the fold formation process
can serve as a gas pool screen by minimum pressure values, necessary for fluids inrush.
That is to say, under absolute permeability of order 10⁻¹⁶ m²
(tenth particles of millidarcy).